FIGURE 1 in A new species of Menestho Møller, 1842 from the Arctic with remarks on Menestho albula (Fabricius, 1780) (Gastropoda: Heterobranchia: Pyramidellidae) ... - Nekhaev, Ivan O. (Zenodo, 2017)
FIGURE 1. Arctic species of Menestho, photographs of shells. A, C, E—Menestho schikovi sp.n.: A—holotype, C—Kara Sea, 76°41'N, 88°14'E, 45 m, E—Laptev Sea, 76°36'N, 118°30'E, 51 m; B—Menestho albula, Barents Sea, Murman Coast, Dalne- Zelenetskaya Bay, 69°07.85'N, 36°04.81'E, 46 m; D—Menestho truncatula, Svalbard, Spitsbergen, Grønfjorden, 77°57'N, 14°16'E. Scale bar = 3 mm. ... : Published as part of Nekhaev, Ivan O., 2017, Zootaxa 4347 (1) , DOI: 10.11646/zootaxa.4347.1.13, http://zenodo.org/record/1044820 ...